The Effect of Flipped Learning on Junior High School Students’ Writing Ability: A Quasi-Experimental Study at SMPN 8 Palangka Raya - Siti Nurrahmah; Sabarun; Akhmad Ali Mirza (Syntax Literate, 2026)
This study examined the effect of WhatsApp-based flipped learning on students’ writing ability at SMPN 8 Palangka Raya through a quantitative quasi-experimental design. It aimed to determine whether there was a significant difference in writing improvement between students taught using WhatsApp-based flipped learning and those taught through conventional methods. The subjects of this study were 64 eighth-grade students selected through cluster random sampling, consisting of an experimental class and a control class. Data were collected through pre-test and post-test writing assessments and analyzed using descriptive statistics, normalized gain (N-gain), normality and homogeneity tests, and an independent samples t-test. The findings revealed that the experimental group achieved higher post-test scores and greater N-gain improvement compared to the control group. The statistical analysis showed a significant difference between the two groups (t (62) = 6.134, p < .001) with a large effect size (Cohen’s d = 1.534). These results indicate that WhatsApp-based flipped learning significantly enhances students’ writing ability. The study concludes that integrating pre-class digital learning through WhatsApp with interactive classroom activities provides a more effective and student-centered approach to improving writing skills, particularly in contexts with limited technological infrastructure.